2011
DOI: 10.1371/journal.pone.0016967
|View full text |Cite
|
Sign up to set email alerts
|

Localized Delivery of Interferon-β by Lactobacillus Exacerbates Experimental Colitis

Abstract: BackgroundThere have been conflicting reports of the role of Type I interferons (IFN) in inflammatory bowel disease (IBD). Clinical trials have shown potent efficacy of systemic interferon-beta (IFN-β) in inducing remission of ulcerative colitis. Likewise, IFNAR1−/− mice display an increased sensitivity to dextran sulfate sodium (DSS)-induced colitis, suggesting Type I IFN play a protective role during inflammation of the gut. Curiously, however, there have also been reports detailing the spontaneous developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 65 publications
(62 reference statements)
0
39
0
Order By: Relevance
“…Though in all of the conducted trials, IFNβ revealed to be safe and well tolerable there are recent case reports that IFNβ treatment in patients with multiple sclerosis was associated with development of IBD [147]. Recent data suggested that IFNγ administration exacerbated colitis in a mouse model of colitis [148]. While the data of the two most recent trials using IFNβ in patients with UC have not been published to date, their results will be of great interest.…”
Section: Human Recombinant Ifnβmentioning
confidence: 99%
“…Though in all of the conducted trials, IFNβ revealed to be safe and well tolerable there are recent case reports that IFNβ treatment in patients with multiple sclerosis was associated with development of IBD [147]. Recent data suggested that IFNγ administration exacerbated colitis in a mouse model of colitis [148]. While the data of the two most recent trials using IFNβ in patients with UC have not been published to date, their results will be of great interest.…”
Section: Human Recombinant Ifnβmentioning
confidence: 99%
“…Another non desired effect of a recombinant Lactobacillus was found when L. acidophilus was engineered to express the interferon- to study the local delivery of this molecule in a colitis mouse model. Surprisingly the administration of the recombinant bacteria secreting IFN- has an immunological effect that resulted in the exacerbation of colitis in this model (McFarland et al, 2011).…”
Section: Engineered Probiotics To Delivery Bioactive Proteinsmentioning
confidence: 80%
“…INF-B1a has different anti-inflammatory mechanisms of action, such as: inhibiting expression of adhesion molecules leading to reduced adhesion of leukocytes and attenuation of inflammatory reactions, downregulation of matrix metalloproteinases, which are implicated in the immunopathogenesis of MS [11][12][13][14][15] and finally inhibiting Th17 cell differentiation known to be a pivotal cell in MS pathogenesis [16]. Conflicting data and paradoxical effects of INF-beta are described in the literature, since in spite of several clinical trials showing promising results in the treatment of UC with INF-B [13], there are various reports of development of UC in patients with MS treated with this drug [17][18][19]. Some authors think that the role of Type I IFN in controlling or exacerbating gut inflammation may be dependent upon factors intrinsic to the patients and this would explain spontaneous development of IBD in some patients receiving IFN-b therapy for MS or hepatitis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting data and paradoxical effects of INF-beta are described in the literature, since in spite of several clinical trials showing promising results in the treatment of UC with INF-B [13], there are various reports of development of UC in patients with MS treated with this drug [17][18][19]. Some authors think that the role of Type I IFN in controlling or exacerbating gut inflammation may be dependent upon factors intrinsic to the patients and this would explain spontaneous development of IBD in some patients receiving IFN-b therapy for MS or hepatitis [13]. Taking into account all these facts, natalizumab, a humanized monoclonal antibody against alfa 4 integrin, was started since this drug is effective in the treatment of either MS and IBD [20,21].…”
Section: Discussionmentioning
confidence: 99%